The Six Sigma way : how to maximize the impact of your change and improvement efforts - Pande, Peter S.; Neuman, Robert P.; Cavanagh, Roland R. (2014)
Explains the impressive benefits of Six Sigma's improvement-driven and customer-centric approach to business leaders and managers. This book reveals how GE, Motorola, and other companies used Six Sigma to fine-tune products and processes, improve performance, reduce costs, build customer loyalty, and increase profits.